Potassium effect on production and forage quality of brachiaria decumbens stapf in the eastern plain piedmont of colombia (2011)
This study was conducted to evaluate the response of planting coffee under different cropping systems: organic, conventional and organic-mineral, on soil phosphorus fractions with volcanic influence in the department of Valle del Cauca (Colombia) coffee growing zone. Sequential fractionation methodology adapted by the International Center of Tropical Agriculture was used. The statistical analysis consisted of a Complete Randomized Block Design under a split plot arrangement with three treatments and three replications. The results showed that contents of the organic fraction of available P and the moderately available P showed significant differences among the systems in which organic and conventional management was included, in which the conventional system had the lowest values. The organic- mineral system showed the highest contents of organic and inorganic phosphorus and the conventional system showed the lowest for these fractions of P. For the non available P fraction, it was found that organic systems had higher P content than the conventional system and, the organic-mineral system showed significant differences with respect to the rest% The total P showed a similar pattern to the fractions described% The low content in the conventional system can be explained by specific aspects of management such as the use of synthetic chemical fertilizers, planting without shade in monoculture and lack of soil coverage between plants.